The evolution of joint teacher observations and reflections as sites of heteroglossia and heteroopia: an actor–network theoretical discussion. Issue 5 (3rd September 2021) - Saito, Eisuke
ABSTRACT: Professional development is increasingly considered key to school reform in many countries. This study was based on the experience of the author in Vietnam, where along with other teachers, the author has been engaged in the attempt to reform schools since 2006. The critical element of this work is for teachers to regularly observe and reflect on classroom practices with one another by focusing on students and their learning. While the author tended to use video recordings for reflection and analysis since the beginning of the collaboration, the teachers in those schools recently started to use their own video recordings on their mobile phones and tablets to share their reflections. This study aimed to discuss the meaning of this evolution from the actor-network theoretical perspective. It will be argued that (1) the right to edit visual evidence to support their narratives was decentralised from the international consultant to the local teachers and that (2) the potential emerged for observed lessons, and possibly joint reflection sessions, to become sites of 'heteroglossia' (multiple voices) and 'heteroopia' (multiple gazes), which allowed the teachers to diversify their understanding of the situation and of student learning and needs.